Peran lingkungan keluarga dalam mengembangkan wirausaha muda - Adi, Khofifatu Rohmah; Idris, Idris (Jurnal Teori dan Praksis Pembelajaran IPS, 2021)
The development and maturity of a person's business is influenced by many factors. Many factors also influence the development of pilot businesses that are started and carried out by students. One of the factors that play an essential role in influencing young entrepreneurs can come from their parents or family environment. This article aims to identify and how the family's role in motivating and developing young entrepreneurs' potential. This research is a qualitative descriptive study. In-depth interviews carried out data collection. The data obtained were then analyzed using interactive analysis techniques, which consisted of 4 stages: data collection, data reduction, data presentation, and concluding. The results showed that entrepreneurial students who had sufficiently developed businesses received much support from their families. Parents' role as a form of support for their children in entrepreneurship is social, instrumental, emotional, and other support. The concrete form of this support is supported in providing facilities for business development, accompanying and assisting the business carried out by their children, giving permission and trust in children. These results can be used as knowledge and input to parents about how they should support children in entrepreneurship. DOI: http://dx.doi.org/10.17977/um022v6i12021p1